Interaction of 4-substituted 5-carbethoxy-6-chloromethylpyrimidin-2-ones with hydrazines and hydrazide derivatives: synthesis and structure - Lebedyeva, І.О.; Povstyanoy, М.V.; Povstyanoy, V.М.; Ryabitskii, A.B.; Panasyuk, O.G. (Украинский химический журнал, 2010)
Reaction of 5-carbethoxy-6-chloromethyl-3,4-dihydropyrimidin-2(1H)-ones with N,N’-binucleophiles has been studied on hydrazine hydrate, monosubstituted hydrazines and carboxylic acid hydrazides. It has been determined that the reaction takes place as nucleophilic substitution of halogen on N,N’-binucleophile followed by the primary pyrimidine heterocyclisation into the pyrrolo[4,3-d]pyrimidine and pyridazino[4,5-d]pyrimidine derivatives. Исследована реакция взаимодействия 5-карбэтокси-6-хлорметил-3,4-дигидропиримидин-2-(1Н)-онов с N,N’-динуклеофилами на примерах гидразингидрата, монозамещенных гидразинов и гидразидов карбоновых кислот. Установлено, что реакция протекает как нуклеофильное замещение галогена N,N’-динуклеофилом с последующей гетероциклизацией исходного пиримидина в производные пирроло[4,3-d]пиримидина и пиридазино[4,5-d]пиримидина. Досліджено реакцію взаємодії 5-карбетокси-6-хлорометил-3,4-дигідропіримідин-2(1Н)-онів з N, N’-динуклеофілами на прикладах гідразингідрату, монозаміщених гідразину і гідразидів карбонових кислот. Встановлено, що реакція проходить як нуклеофільне заміщення галогену N,N’-динуклеофілом з наступною гетероциклізацією вихідного піримідину в похідні піроло[4,3-d]піримідину та піридазино[4,5-d]піримідину.